Análisis Y diseño curricular de la asignatura instrumentación industrial de la Universidad de la Costa C.U.C. (2017)
The industry and the automatized process require of instruments and technologies which are in a constant innovation. The institutions of high education, the professionals in the electronic domain and the industrial sector are conscious about the needs of updating the area of industrial instrumentation. The institutions of education should train their students according to the requirements of industrial sector whereby is necessary update continuously their course contents. In this project, we present the studies for the updating the Industrial Instrumentation course of Universidad de la Costa (CUC). First, we analyze the national context of industry and evaluate of Industrial Instrumentation curricular structure of Universidad de la Costa and other national and international universities. Finally, we suggest an update of contents and teaching-learning methodologies for the industrial instrumentation course program in the electronic engineering program of Universidad de la Costa, CUC.